Impact of CSR Criteria and Sub-Criteria on Retailer Personality: A Study using AHP - Rashid, Abdul; Rokade, Varsha (Prabandhan: Indian Journal of Management, 2019)
The retail industry accounts for about 10% percent of the total GDP of India and the retail industry generates around 8% of the total employment. An objective of this study was to analyze the relative importance of different CSR criteria on retailer personality in organized retail. Data were gathered from experts through specially designed AHP questionnaire and analyzed using the pairwise comparison through AHP. Weights for three CSR criteria, that is, environmental responsibility, societal responsibility, and philanthropic activities were determined. Hierarchical structure was developed to depict the relative importance of each criterion and sub-criteria of CSR. The results revealed that criterion of societal responsibility of CSR had maximum impact on building retailer personality, while criterion of environmental responsibility had minimum impact. In sub criteria comparison, no selling of cigarettes and tobacco had maximum impact on retailer personality, while solar energy use had minimal impact. Implications and recommendations were suggested to retail managers.